Epidemiologia da ferrugem asiática da soja em ambientes do Estado de Goiás: efeito de fungicida e época de semeadura - CRUVINEL, Adriane Reis (2005)
During the last crops, the soybean rust has been appeared as one of the most important problems in the national agriculture. The direct loses on the production and in the costs with fungicides have been increased the damages on this crop. Aiming to understand better the disease epidemiology, this work searched for answers by epidemic progress in two locations, the time of planting effect, the cycle of planting, the use of fungicide, and by different cultivars. The experiments were assembled in Experimental Stations from Agência Rural in Senador Canedo and in Anápolis. For each place were used three times of planting, six cultivars on the three crop cycles (Monsoy 6101 and BRSNina premature cycle; Emgopa 315 and BRSGO Santa Cruz middle cycle; Emgopa 313 and BRSGO Paraíso late cycle), with and without fungicide action, have been evaluated on the three parts of the plant (lower, middle and upper). Each time, to each one of the places, have been considered as an experiment with spli-split-plot. After the disease symptom observations, the split under chemical control were freaked each 21 days using pyraclostrobin+epoxiconazole on 66,5 g + 25 g a.i. ha-1. The evaluations, after the first symptom observation, have been done weekly up to the complete leaves took away. With the periodic severity data the Area Under Progress Disease Curve (AUPDC) and Relative Area Under Progress Disease Curve (RAUPDC), that is the area divided by the epidemic time duration, were calculated. The parameters were productivity, thousand-grains weight (TGW) and small grains percent (%SG). The delay on the start of the disease on Anápolis, comparing with Senador Canedo, increases the discussion on the results. The previous disease occurrence in Senador Canedo and the high level inoculate presented can be associated to the fact of experimental site in Senador Canedo has soybean cultivate all over the year. The delay on the start of the disease on Anápolis, compared to Senador Canedo has been resulted on productivity increase and fungicide effect decrease. Comparing the time of planting in both planting places, the second one presented the highest level of severity, but the highest level of productivity even. The use of fungicide decrease significantly the AUPDC, increase the productivity, the TGW and decrease the %SG. The premature cycle cultivars presented lowest disease severity. The cultivar Emgopa 315 although be a medium cycle presented results equals premature cycles cultivars. On each site the time of planting were differentiated. On high pressure inoculate condition the difference between evaluated factors was lower. On lower inoculate pressure the evaluated factors expressed better the changes. As conclusion we have: a) how early the disease appears higher is your effect on productivity; b) using premature cultivars the escape effect decrease the disease damages when compared to medium and late cycle; c) the disease decrease the soybean cycle by the defoliation; d) although all the cultivars presented susceptibility to rust, related to lower severity on partial resistance; e) the fungicide utilization pyraclostrobin+epoxiconazole on de 66,5 g + 25 g a.i. ha-1, used on first symptom and in 21 on 21 days decrease the disease progress and the effects on productivity; f) the disease progress decrease by fungicide utilization is better in late planting; g) under the fungicide effect pyraclostrobin+epoxiconazole with 66,5 g + 25 g a.i. ha-1 there s no variation time planting and site; h) under high inoculate pressure the variation between time planting on disease progress and productivity is lower; i) the time of planting must be considered but not lonely, always in association with others factors of fungus action; j) the use of RAUPDC is necessarily when there is variation the time of soybean cycle, affecting the rust epidemic duration; l) the highest disease level occurs on the part of the plant near the soil and the defoliation difficult the disease evaluation on this part of the plant; m) the most effective disease occurs on the highest parts of the plant.